CLUSTER ANALYSIS FROM A RESEARCH STUDY ON DIGITAL COMPETENCES IN UNIVERSITY PROFESSORS - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aimed to analyze the relationship between variables: sex, academic degree, teaching experience, age, and type of employment contract, with the digital skills from university professors in the Sucre Department in Colombia. The questionnaire from Agreda et al., (2016) was applied to a sample of 354 professors made up of four dimensions: 1. Use and technological literacy, 2. Educational methodologies through Information and Communication Technologies in the classroom (ICT), 3. Training of university professors in ICT and attitude towards ICT in higher education. For the information analysis, a segmentation process was carried out through cluster analysis. As a result, it could be established that the segment configuration through the clusters in each dimension suggests that there is no relationship between the variables: sex, academic degree, teaching experience, and type of employment contract with the dimensions of digital skills from the studied professors. There is only evidence of a relationship with the age variable, seemingly showing that younger professors have better digital skills than the older ones.